Secondary Cell Wall Polymers of Enterococcus faecalis Are Critical for Resistance to Complement Activation via Mannose-binding Lectin - Geiss-Liebisch, Stefan (American Society for Biochemistry and Molecular Biology, 2012)
The complement system is part of our first line of defense against invading pathogens. The strategies used by Enterococcus faecalis to evade recognition by human complement are incompletely understood. In this study, we identified an insertional mutant of the wall teichoic acid (WTA) synthesis gene tagB in E. faecalis V583 that exhibited an increased susceptibility to complement-mediated killing by neutrophils. Further analysis revealed that increased killing of the mutant was due to a higher rate of phagocytosis by neutrophils, which correlated with higher C3b deposition on the bacterial surface. Our studies indicated that complement activation via the lectin pathway was much stronger on the tagB mutant compared with wild type. In concordance, we found an increased binding of the key lectin pathway components mannose-binding lectin and mannose-binding lectin-associated serine protease-2 (MASP-2) on the mutant. To understand the mechanism of lectin pathway inhibition by E. faecalis, we purified and characterized cell wall carbohydrates of E. faecalis wild type and V583ΔtagB. NMR analysis revealed that the mutant strain lacked two WTAs with a repeating unit of →6)[α-l-Rhap-(1→3)]β-d-GalpNAc-(1→5)-Rbo-1-P and →6) β-d-Glcp-(1→3) [α-d-Glcp-(1→4)]-β-d-GalpNAc-(1→5)-Rbo-1-P→, respectively (Rbo, ribitol). In addition, compositional changes in the enterococcal rhamnopolysaccharide were noticed. Our study indicates that in E. faecalis, modification of peptidoglycan by secondary cell wall polymers is critical to evade recognition by the complement system.